Highly Enantioselective Construction of 3‐Hydroxy Oxindoles through a Decarboxylative Aldol Addition of Trifluoromethyl α‐Fluorinated gem‐Diols to N‐Benzyl Isatins1. Issue 21 (15th April 2013) - Saidalimu, Ibrayim; Fang, Xiang; He, Xiao‐Peng; Liang, Jing; Yang, Xueyan; Wu, Fanhong
<x xml:space="preserve">Abstract</x> An organocatalytic asymmetric direct aldol addition reaction that involves cleavage of a carbon–carbon bond through the release of trifluoroacetate was developed. The protocol is wide in scope, generating the desired oxindoles of biological interest in nearly quantitative yields (up to 99 %) with excellent enantioselectivities (up to 98 % ee) and diastereoselectivities (up to 99:1 d.r.).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>